A study on FRAME model: Evidence from banking industry - Fazlollah Talebi; Maryam Sasaniyan (Management Science Letters)
The Framework for the Rational Analysis of Mobile Education (FRAME) model explains mobile learning features as a process in terms of mobile technologies, human learning capacities, and social interaction. It describes various issues of information overload, knowledge navigation, and cooperation in learning. The framework gives insight for development of future mobile devices as well as learning materials, and an appropriate design of learning and teaching strategies for the purpose of mobile education. The proposed study of this paper implements the FRAME model in Iranian banking industry. The study has been implemented among a sample of 160 regular employees who worked for Bank Maskan in province of Alborz, Iran. To validate the questionnaire, we use content validity ratio (CVR) and verify the questionnaire using Cronbach alphas. Using t-student test, the study has determined that the firm was ready to adopt mobile learning in terms of device, social and learner aspects. In our survey, learner aspect was number one priority followed by device and social aspects.